Dietary administration of sodium alginate ameliorated stress and promoted immune resistance of grouper Epinephelus coioides under cold stress. Issue 65 (June 2017) - Lee, Pai-Po; Lin, Yu-Hung; Chen, Min-Chieh; Cheng, Winton
Abstract: Grouper, Epinephelus coioides, fed a diet containing sodium alginate at 0 (control, named C) and 1.0 g kg −1 (named S) at a temperature of 28 °C for 12 days, were then further individually transferred to 28 (two groups named C-28 and S-28) or 20 °C (two groups named C-20 and S-20), and immune parameters and stress indexes were measured at the beginning and after 6, 12, 24 and 48 h of exposure. Examination of immune parameters revealed that the alternative complement activity (ACH50 ), lysozyme activity, phagocytic activity, superoxide dismutase, and respiratory bursts significantly increased in groupers fed the sodium alginate-containing diet for 12 days, and were higher in the S-28 than those of the C-28 and S-20 groups, which were higher than those of the C-20 group from 6 to 48 h except for ACH50 at 48 h, respiratory bursts at 48 h, and lysozymes at 6 h. For the assessment of stress indicators, cortisol, glucose, and lactate levels of serum significantly decreased in grouper fed the sodium alginate-containing diet for 12 days, and were higher in the C-20 group than those of the C-28 and S-20 groups, which were higher than those of the S-20 group at 6–48 h. In another experiment, grouper fed the test diet for 12 days at a temperature of 28 °C were challenged with Photobacterium damselae subsp. piscicida at a dose of 5 × 10 3  colony-forming units (cfu) (g fish) −1, and then individually transferred to 28 or 20 °C. The survival rate of challenged fish of the C-28 group was significantly lower than those of challenged fish of the C-20 and S-28 groups, which were significantly lower than that of challenged fish of the S-20 group. All challenged fish of the S-20 group survived. Survival rates over 144 h were 30.0%, 70.0%, and 56.7% for the C-28, C-20, and S-28 groups, respectively. Our results indicated that dietary sodium alginate administration downregulated stress response indicators, enhanced immune responses, and prevented impacts of physiologic stress responses, immunosuppression, and susceptibility to P. damselae subsp. piscicida in grouper subjected to cold stress. Grouper cultured at 28 °C were more susceptible to P. damselae subsp. piscicida infection. Highlights: Grouper fed a sodium alginate-containing diet upregulate anti-stress and immune responses. Impacts of physiologic stress, immunosuppression under cold-shock stress were ameliorated. The susceptibility against infection at 28 °C can be decreased by sodium alginate feeding.